Application of Immunohistochemistry in Thyroid Pathology - Liu, Haiyan; Lin, Fan (Archives of pathology & laboratory medicine (1976), 2015)
Accurate classification of follicular-patterned thyroid lesions is not always an easy task on routine surgical hematoxylin-eosin-stained or cytologic fine-needle aspiration specimens. The diagnostic challenges are partially due to differential diagnostic criteria that are often subtle and subjective. In the past decades, tremendous advances have been made in molecular gene profiling of tumors and diagnostic immunohistochemistry, aiding in diagnostic accuracy and proper patient management. To evaluate the diagnostic utility of the most commonly studied immunomarkers in the field of thyroid pathology by review of the literature, using the database of indexed articles in PubMed (US National Library of Medicine) from 1976-2013. Literature review, authors' research data, and personal practice experience. The appropriate use of immunohistochemistry by applying a panel of immunomarkers and using a standardized technical and interpretational method may complement the morphologic assessment and aid in the accurate classification of difficult thyroid lesions.